Chemical constituents of Kalanchoe pinnata / Ishak Zakaria @ Ali - Zakaria @ Ali, Ishak (Faculty of Applied Sciences, 2008)
Kalanchoe pinnata is an erect shrub plant that is very useful for the treatment of diseases. The common name of this plant is Setawar. This plant is a very good medicinal plant to treat fever, diarrhea, vomiting and others. There are many chemical constituents contained in this plant. The steroids from the leaves of Kalanchoe pinnata were extracted with dichloromethane. Chromatographic methods were also used to isolate the mixture of steroids. The weight of crude steroids obtained was 0.0lg from 80.4g of grounded leaves of Kalanchoe pinnata. The structures of the steroids were identified by Gas Chromatography-Mass Spectrometry. The steroids found in this study were campesterol (ergost-5-en-ol), stigmasterol (stigma-5, 22- dien-3-ol), and (3-sitosterol ((23S)-ethylcholest-5-en-3|3-ol).